ANALISIS USER EXPERIENCE DAN USER INTERFACE PEGADAIAN SYARIAH DIGITAL MOBILE DENGAN METODE USER CENTERED DESIGN DAN SYSTEM USABILITY SCALE (SUS) - Nio Dimas Radityo (2023)
Pegadaian Syariah is a business unit of PT Pegadaian, a government-owned financial institution. Pegadaian Syariah does not only provide pawn-based products, but also provides other financing services with sharia principles. In carrying out its transactions, Pegadaian Syariah uses various media, both digital and conventional, to make it easier for the community. Pegadaian Syariah has an application called Pegadaian Syariah Digital Mobile to make mortgage applications, gold transactions, and make payments that can be downloaded through the App Store and Play Store. With the Pegadaian Syariah Digital Mobile, it is hoped that it will make it easier for customers to make pawn transactions anywhere and anytime. However, this must be supported by a good, attractive and user-friendly interface so that the application is easy for users to understand. This study aims to analyze and provide an assessment of the user experience and to redesign the appearance of the user interface so that it can fulfill the usability value of the Pegadaian Syariah Digital Mobile application by applying the User Centered Design (UCD) method. The application of the UCD method was carried out by carrying out questionnaires and prototyping with the System Usability Scale (SUS) technique. This research will produce a new interface in the form of a prototype that can be used as a suggestion for Pegadaian Syariah.